Evolution of carbon diffusion layer to oxidation film during cathodic plasma electrolysis on steel. Issue 1 (2nd January 2020) - Wu, Jie; Lu, Ping; Dong, Lei; Zhao, Mengli; Li, Dejun; Xue, Wenbin
ABSTRACT: In this paper, a systematical research of the cathodic plasma electrolysis process on steel materials was carried out. The plasma electrolytic saturation and oxidation were integrated together. The evolution of carbon diffusion layer to oxidation film from the critical voltage to the oxidation voltage was investigated. The results showed that there was a significant increase of steel surface temperature at the critical voltage, accompanied by a grain refinement near the interface. Above the critical voltage, the carburizing process started. The carbon diffusion coefficient at 380 V was 1.5 × 10 −7  cm 2  s −1, which was one order of magnitude higher than that of the traditional carburizing at the same temperature. As the voltage rising, the activity of oxygen species increased and the carburizing process was replaced by an oxidation process. Meanwhile, the carbon atoms were released from the interstitial sites and gradually aggregated into carbon particles, embedded in the oxide layer on steel surface.